Examination of Zinc Oxide Films Prepared by Magnetron Sputtering. (2016) - Dave, Pranav Y.; Patel, Kartik H.; Chauhan, Kamlesh V.; Chawla, Amit Kumar; Rawal, Sushant K.
Abstract: Nano-structured zinc oxide thin films were deposited on corning glass substrate by magnetron sputtering process. Zinc oxide films were deposited at different gas ratio values of argon:oxygen kept at 2sccm:18sccm, 6sccm:14sccm, 10sccm:10sccm and 14sccm:6sccm. X-ray Diffraction (XRD) technique was used to characterize ZnO thin films. The XRD graphs indicate presence of (100) and (002) peaks for ZnO thin films. Contact angle and surface energy of nano-structured ZnO thin films were determined by contact angle goniometer. Zinc oxide films are hydrophobic by nature and their contact angle value varies from 98.3° to 102.1° with decrease in flow rate of oxygen gas and increase in argon gas flow rate. UV-Vis-NIR spectrophotometer was used to characterize optical properties of ZnO thin films.